Role of Acetazolamide in Traumatic CSF Rhinorrhea and Otorrhea: A Randomized Controlled Trial - Madeshiya, Shivam; Srivastava, Chhitij; Ojha, Bal Krishan; Chandra, Anil; Jaiswal, Somil; Bajaj, Ankur; Yadav, Awadesh (Asian Journal of Neurosurgery, 2024)
Background Untreated cerebrospinal fluid (CSF) rhinorrhea and otorrhea can lead to adverse complications like meningitis and hence should not be overlooked. Acetazolamide reduces CSF production by 48%. The actual role of acetazolamide in the amelioration of traumatic CSF rhinorrhea and otorrhea is not clear as, till date, very few formal studies have been conducted. Aim of the study was to determine the role of acetazolamide in traumatic cerebrospinal fluid rhinorrhea and otorrhea.Materials and Methods A randomized controlled trial was conducted among 134 patients with head injuries presenting to the neurosurgery department of a tertiary care center in North India, with complaints of CSF rhinorrhea and otorrhea within 72 hours of traumatic injury. One-hundred thirty-four patients were randomized into intervention and control group. Comparative analysis was not possible in 58 patients as in due course they were either operated for head injury or lumbar drain was put due to excessive CSF leak; hence, forth comparative analysis was done in 76 patients. Out of these 76 patients, 44 patients belonged to the intervention group (Acetazolamide given) and 32 belong to the control group (Acetazolamide not given). The day of the stoppage of CSF Leak was the main endpoint of this study.Result Majority of the patients were in the age group of 21 to 30 years and were predominantly males. Road traffic accident was observed in 84 (75%) patients. There was no statistically significant difference noted in the mean number of days of CSF leak whether acetazolamide was given or not (p = 0.344). The complication associated with CSF leak was meningitis. The percentage of patients developing meningitis was more after lumber drain insertion.Conclusion In our study, there was no advantage of adding acetazolamide to the conservative management of traumatic CSF leak. Therefore, the practice of routinely giving acetazolamide should be reconsidered.
Keywords: acetazolamide; meningitis; cerebrospinal fluid rhinorrhea and otorrhea